An omic and multidimensional spatial atlas from serial biopsies of an evolving metastatic breast cancer - Johnson, Brett E.; Creason, Allison L.; Stommel, Jayne M.; Keck, Jamie M.; Parmar, Swapnil; Betts, Courtney B.; Blucher, Aurora; Boniface, Christopher; Bucher, Elmar; Burlingame, Erik; Camp, Todd; Chin, Koei; et al. (Cell reports. Medicine, 2022)
Mechanisms of therapeutic resistance and vulnerability evolve in metastatic cancers as tumor cells and extrinsic microenvironmental influences change during treatment. To support the development of methods for identifying these mechanisms in individual people, here we present an omic and multidimensional spatial (OMS) atlas generated from four serial biopsies of an individual with metastatic breast cancer during 3.5 years of therapy. This resource links detailed, longitudinal clinical metadata that includes treatment times and doses, anatomic imaging, and blood-based response measurements to clinical and exploratory analyses, which includes comprehensive DNA, RNA, and protein profiles; images of multiplexed immunostaining; and 2- and 3-dimensional scanning electron micrographs. These data report aspects of heterogeneity and evolution of the cancer genome, signaling pathways, immune microenvironment, cellular composition and organization, and ultrastructure. We present illustrative examples of how integrative analyses of these data reveal potential mechanisms of response and resistance and suggest novel therapeutic vulnerabilities. [Display omitted] •Safe and reliable workflows for multiplatform measurements from single biopsies•Clinical metadata with 11 omic and imaging assays from serial biopsy and blood•Omic, cellular, and structural evolution of metastatic cancer in a single individual•Integrative analyses reveal new potential mechanisms of response and resistance Identifying mechanisms of response and resistance to treatment in individual cancer patients is challenging but critical for improvement of precision medicine outcomes. Johnson et al. report a comprehensive atlas from a single individual with breast cancer and demonstrate how longitudinal, integrative analyses can provide new insights.